A socio legal study on the film censorship law and regulations in controlling film release for public screening in Malaysia / Siti Sarah Sahaimi ... [et al.] - Sahaimi, Siti Sarah; Rosli, Aina Amarlina; Samsudin, Nur Farahin; Ismail, Nurul Hidayat (2010)
Censor is commonly known as the act of removing any part of art work that is considered indecent or that it might offend people if it is released for public viewing. Censoring a film specifically refers to the act of removing certain scenes in the film itself so that the film that is released is suitable for public viewing at large. In Malaysia, the Film Censorship Board under the Home Ministry is the body responsible for censoring a film before it is released for public viewing. It is undeniable that films need to be examined because the content somehow can transmit evil ideology. This is because films are attractive and have the strong ability to influence thousands of viewers at one time. However, the act of censoring film by the Film Censorship Board sometimes creates dissatisfaction among film producers and the public as well. This is because the guidelines that are used by the Board are not specific with regards to the extent and limitation of censorship. This causes the credibility of the Board to be frequently questioned. Apart from that, there is no sense of balance in the standard requirements and qualifications for the release of international films for local screening as compared to the release of local films. Consequently, local films are said to be jeopardised for there are more scenes that are censored compared to those of foreign ones. This paper therefore scrutinizes all the laws and regulations that are applied by the Film Censorship Board and provides a clear view with regards to the limits and extent of the said laws. This paper will also discuss and compare the enforcement of the censorship laws to local and foreign films.